Mapping and Visualizing Research Output on Global Solid Waste Management: A Bibliometric Review of Literature. Issue 2 (3rd April 2022) - Rahaman, Md Safiqur; Ansari, Khadeeja M. N.; Kumar, Hardesh; Shah, Karnika
ABSTRACT: Solid waste management refers to collecting, treating, and disposing of solid waste that has served its purpose or is no longer useful. The primary purpose of this research is to map and visualize the solid waste management literature indexed on the Web of science between 1966 and 2021 based on bibliometrics analysis. This study also identified the most productive authors, sources, organizations, countries, research areas, funding agencies etc. This study employed the bibliometric method to analyze global research productivity on solid waste management literature. A total of 4444 research papers downloaded from the Web of science during the study period. Bibliometrics software, namely Bibexcel, VOSviewer, Biblioshiny, and Microsoft Excel, used to analyze the data. The results show that there was 4444 publication with 78759 citations between 1966 and 2021. The maximum number of papers, i.e., 424 published in 2020, in 1966 single paper published and received one citation. The journal W aste management published 382 papers and became the most relevant source of the topic, whereas Huang GH recognized as the most prolific author with 214 papers. China contributed a significant number of research papers in the field, while the University of Regina, Canada, emerged as a top-performing institution. China and Canada together collaborated more in producing literature in solid waste management. The study concludes that there is a need for further bibliometric study of other related topics in waste management, such as liquid waste management and gasses waste management.